An Islamic Perspective of Psychological Resilience: Case Study of The Tsunami Survivors in Aceh - Rineza Risky; Eka Srimulyani; Marty Mawarpury (Program Studi Psikologi, Fakultas Kedokteran, Universitas Syiah Kuala, 2023)
This study was designed to examine the Islamic point of view and the role of Islam, particularly the disaster resilience, within the tsunami survivors in Aceh. This qualitative research involved 30 respondents who were the tsunami survivors from Aceh Jaya, Great Aceh and Banda Aceh. The data collection was accomplished by conducting interview and documentation. Those exposed that Islam played a vital role in forming their resilience since the victims believed that, in the view of Islamic perspective, the calamity and natural disaster occurred were the tests for their faith on Islam. This belief, which was based on their devotion to Allah, the Almighty, grew a well-formed resilience among the survivors.